Impact of irrigation levels and mulching on yield and nutrient uptake of okra cultivars under various planting geometry - Choudhary, Santosh; Chandra, Atul; Yadav, P.K. (Annals of Agricultural Research, 2014)
A field experiment was conducted during rainy season (2009), at College of Agriculture, Bikaner to find out the effect of crop geometry on growth, yield and nutrient uptake of okra (Abelmoschus esculentus L. Moench) cultivars under different irrigation levels and mulching. Results indicated that irrespective of irrigation levels, cultivars and mulches higher growth attributes, pod yield/ plant (127 g) and N,P,K uptake (87.5, 15.1, 94.1, respectively) were recorded under wider spacing (75 cm x 40 cm) except, the pod yield/ha (15.9 t/ha) which was higher under closer spacing (40 cm x 20 cm). The growth attributes of okra viz., plant height, leaves/plant, branches/plant and dry weight of leaves were recorded significantly higher at 1.0 V of drip irrigation. However, 0.6 V of drip irrigation recorded significantly highest biomass accumulation, pod yield/plant, pod yield/ha (18.5 and 16.5 t/ha at 40 cm x 20 cm and 75 cm x 40 cm spacing, respectively) and N, P and K uptake of okra. Among cultivars, ’Tulsi’ registered significantly higher growth, yield and N, P and K uptake. Among mulches organic mulch produced significantly maximum growth attributes, pod yield/ha (17.4 and 15.6 t/ha at 40 cm x 20 cm and 75 cm x 40 cm spacing, respectively) and uptake of N, P and K over mulches.